PENGARUH KARAKTERISTIK TUJUAN ANGGARAN DAN PENGENDALIAN INTERNAL TERHADAP KINERJA APARAT PEMERINTAH DAERAH (Studi Empiris Pada SKPD Kabupaten Kampar) - Haryanti Ismalia; Taufeni Taufik; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the influence of empirical evidence budgetary participation, budget goal clarity, feedback, evaluation of the budget, the budget goal difficulty, and internal control over the performance of local government officials Kampar regency. This research was conducted by using a survey of local work unit Kampar regency. The population in this study is 31 working units Kampar regency. Samples taken amounted to 93 respondents. The type of data used are primary data with data collection method using a questionnaire. Data analysis method used in this study. The results showed that the Budget Participation significant effect on the performance of local government officials. Clarity of purpose budget has no significant effect on the performance of local government officials. Umpan behind budget significantly affect the performance of local government officials. Evaluation budget significantly affect the performance of local government officials. Difficulty budgetary purposes does not affect the performance of local government officials and Internal Control influence on the performance of local government officials . Based on the calculation of the coefficient of determination (R2) obtained a value of 0.717. This shows that the influence of the independent variables on the dependent 71.7% and the remaining 28.3% influenced by other variables.Keywords: Characteristic, budget, internal control, performance and government.